Obat-obat intrakanal yang digunakan pada perawatan saluran akar=lntracanal medicaments used in root canal treatment - Sam'an Malik, Masudi; Witjaksono, Widowati (Airlangga University Press, 2001)
The successful outcome of root canal treatment (RCT) depends on the reduction or elimination of bacteria presence in the root canals. Biomechanical preparations of the root canal comprise the most important phase of the RCT. However, other aspects of treatment cannot be neglected because they are all interelated and contribute to the success of RCT. Instrumentation of the root canal physically reduces the number of bacteria significantly and Sodium hypochloride irrigation reduces them again by 50%.Medicated interim dressing used after instrumentation and irrigation can kill the remaining microorganism and prevent reinfection. This presentation focuses on the Intracanal medicaments used in RCT. Chemical and therapeutic agents commonly used in RCT are: chelating agents, irrigation solutions, intracanal medications and systemic antibiotics. Some of these medicaments (particularly phenolics) are antigenic and cytotoxic and they are effective for only short time. Calcium Hydroxide is the most effective and a recommended antimicrobial agent in RCT.